2017
DOI: 10.15640/ijhs.v5n2a6
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Physical Environments on University Student Eating Behaviors

Abstract: Faced with rising tuition costs and limited financial means, university students experience a range of physical environments that can have an impact on their eating behaviors and health. Data was gathered from 188 students from two Canadian east coast universities to determine relationships between their day to day living and eating arrangements and self-reported three day food frequency intakes. Hypotheses testing with bivariate analyses were conducted. Students had a range of living arrangements, only 15% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…On the contrary, Gonzales (2013) in his study on the impact of residence on dietary intake, food insecurity, and eating behavior among university undergraduate students revealed that residence type (on-campus, offcampus, and family home) did not have any impact on the dietary behaviour of students. Furthermore, issues related to living arrangements and eating behaviour among students seem exaggerated according to Mann and Blotnicky (2017) as healthy eating is only slightly influenced by type of residence (with parents, in apartments, or on-campus).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Gonzales (2013) in his study on the impact of residence on dietary intake, food insecurity, and eating behavior among university undergraduate students revealed that residence type (on-campus, offcampus, and family home) did not have any impact on the dietary behaviour of students. Furthermore, issues related to living arrangements and eating behaviour among students seem exaggerated according to Mann and Blotnicky (2017) as healthy eating is only slightly influenced by type of residence (with parents, in apartments, or on-campus).…”
Section: Introductionmentioning
confidence: 99%